Effects of Job Mismatch in Job Satisfaction of Bpo Employees at Fairview Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The job satisfaction of BPO employees has been a topic of significant interest in recent years,given the fast-paced and high-pressure nature of the work environment. BPO or BusinessProcess Outsourcing is a growing industry in which companies outsource various businessfunctions, such as customer service, telemarketing, and technical support, to third-partyservice providers. Research suggests that job satisfaction among BPO employees isinfluenced by several factors, including the nature of the job itself, the work environment, therelationship with colleagues and supervisors, compensation and benefits, and opportunitiesfor growth.Most of the respondents are 26-30 years old, working in BPO with 4-6 years in service, andthe respondents are college graduates. The survey researchers provided the "Effect of jobmismatch in job satisfaction on the employer's salary, work environment, compensation,benefits, and co-workers relationship'" the data says they are very satisfied with their jobs asBPO employees. Who is most likely to have job satisfaction in terms of sex based on theresult? Men were very satisfied with their job and got a mean score of 3.37, while femaleswere satisfied only and got a mean score of 3.02. Based on the findings of the studies and theresults.The researchers recommend conducting a seminar for fresh graduates and job seekers andinviting a speaker to the seminar to promote or inform about our research entitled The Effect ofJob Mismatch on Job Satisfaction of BPO Employees. The Job Mismatch no longer affectstheir satisfaction in their job, and working in BPO, even if you are a fresh graduate, is fine aslong as you know that you are happy and satisfied.
Keywords: Social Sciences